A6: Tapering and Withdrawal of Tocilizumab in Patients With Systemic Juvenile Idiopathic Arthritis in Inactive Disease: Results From an Alternative Dosing Regimen in the TENDER Study. Issue 11 (March 2014) - De Benedetti, Fabrizio; Ruperto, Nicolino; Brunner, Hermine; Grom, Alexei A.; Wulffraat, Nico; Henrickson, Michael; Jerath, Rita; Kimura, Yuki; Kadva, Alysha K.; Wang, Jianmei; Martini, Alberto; Lovell, Daniel J.
Abstract : Background/Purpose: The TENDER clinical trial is a 3‐part, 5‐year, phase 3 study with tocilizumab (TCZ) in patients with active systemic juvenile idiopathic arthritis (sJIA). After 2 years of treatment, sJIA patients who have maintained clinically inactive disease for 3 months are given the option to participate in an alternative TCZ dosing regimen aimed at spacing the infusions and eventually withdrawing TCZ. Herein we describe the patients registered to participate in the optional alternative dosing schedule in the TENDER study. Methods: To qualify for the optional alternative dosing schedule, patients had to be in the study for 2 years and had to achieve American College of Rheumatology JIA inactive disease status. Among the 112 patients enrolled, 39 (35%) entered the optional alternative dosing regimen. This entailed a staged prolongation of the time interval between TCZ infusions from 2 weeks (standard interval) to 3 weeks, then 4 weeks, with the option of terminating TCZ after the discontinuation of any treatment. Results: Twenty‐three male and 16 female patients entered the optional alternative dosing schedule. Their mean baseline characteristics were 14.2 active joints, 15.4 joints with limitation of motion, physician global VAS score of 58.5, CHAQ‐DI score of 1.62, and erythrocyte sedimentation rate (ESR) of 56.8. Fifteen had fever. Of these 39 patients, 13 patients lost clinically inactive disease status while on the optional alternative dosing schedule. In these 13 patients, the time to loss of inactive disease status ranged from 1.4 to 16.8 months from initiation of the optional alternative dosing schedule (n = 4 on 3‐week dosing; n = 6 on 4‐week dosing; n = 3 off TCZ). Risk for losing inactive disease status on the optional alternative dosing schedule was similar in patients treated with methotrexate (6/16, 37.5% flared) and in those not treated with methotrexate (7/23, 30.4% flared). Inactive disease status was maintained in 26 of the 39 patients entering the optional alternative dosing schedule. Dosing intervals were every 3 weeks in 3 patients and every 4 weeks in 14 patients; 9 patients have been able to discontinue TCZ (range of time since discontinuation: 3.6–13.4 months). At baseline, these 9 patients were clinically similar to other patients entering the optional alternative dosing schedule (mean characteristics: age 9.1 years, 10.9 active joints, 10.9 joints with limitation of motion, physician global VAS score of 45.4, CHAQ‐DI score of 1.4, ESR of 47.2; 4 patients with fever at baseline). Conclusion: Patients with sJIA who maintain clinically inactive disease status can progressively space TCZ infusions, with one‐fourth of them able to discontinue all treatments, including TCZ.